2017
DOI: 10.1002/ana.24840
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation at 16q24.2 is associated with small vessel stroke

Abstract: Objective Genome-wide association studies (GWAS) have been successful at identifying associations with stroke and stroke subtypes, but have not yet identified any associations solely with small vessel stroke (SVS). SVS comprises a quarter of all ischaemic stroke and is a major manifestation of cerebral small vessel disease, the primary cause of vascular cognitive impairment. Studies across neurological traits have shown younger onset cases have an increased genetic burden. We leveraged this increased genetic b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
48
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 79 publications
(49 citation statements)
references
References 52 publications
0
48
1
Order By: Relevance
“…Common etiological subtypes of ischemic stroke include large-artery atherosclerotic stroke (LAS), cardioembolic stroke (CES), and stroke caused by small-vessel disease (small-vessel stroke (SVS)), which is also the leading cause of ICH. Previous genome-wide association studies (GWAS) in predominantly European-ancestry groups have identified ten loci robustly associated with stroke 312 . In most instances, the associations with stroke were attributed to individual subtypes of ischemic stroke, such as LAS 5,8,9 , CES 3,4 , and SVS 10,12 , or of ICH 6 , although some loci were associated with two or more stroke subtypes 7,9,11,13 or with any stroke 10 .…”
mentioning
confidence: 99%
“…Common etiological subtypes of ischemic stroke include large-artery atherosclerotic stroke (LAS), cardioembolic stroke (CES), and stroke caused by small-vessel disease (small-vessel stroke (SVS)), which is also the leading cause of ICH. Previous genome-wide association studies (GWAS) in predominantly European-ancestry groups have identified ten loci robustly associated with stroke 312 . In most instances, the associations with stroke were attributed to individual subtypes of ischemic stroke, such as LAS 5,8,9 , CES 3,4 , and SVS 10,12 , or of ICH 6 , although some loci were associated with two or more stroke subtypes 7,9,11,13 or with any stroke 10 .…”
mentioning
confidence: 99%
“…This SNP has previously been found to be associated with immune markers such as myeloid white cell/ neutrophil count (Astle et al 2016), as well as with tonsillectomy (Pickrell et al 2016). Furthermore, the same SNP has been associated with conditions such as coronary artery disease (Pickrell et al 2016), shown suggestive association to ischemic stroke (Traylor et al 2017), and been connected to metabolic traits such as fasting glucose levels (Wessel et al 2015). Some of these traits, namely the immune markers, are related to infection and could potentially be on some pathway together with the infection phenotype in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Our meta-analysis discovered a high number of significant SNPs, genes and loci that are only associated with PVWMH, more than any single total WMH GWAS to date. Most genes and loci previously reported as significant in total WMH 29,30,32,37,39 were found to be associated with PVWMH alone, including PLEKHG1 29 , SH3PXD2A 17,41,48 and COL4A2 48 . Most of the genes associated with PVWMH have direct effects on vascular function, or with vascular diseases such as ischemic stroke, intracranial hemorrhage or coronary artery disease.…”
Section: Discussionmentioning
confidence: 93%